Effect of Hyaluronic Acid on the Activity of Methylene Blue in Photogeneration of 1O2 - Valeriya V. Kardumyan; Anastasia S. Kuryanova; Aleksandr V. Chernyak; Nadezhda A. Aksenova; Mikhail V. Biryukov; Nicolay N. Glagolev; Anna B. Solovieva (Molecules)
The effect of a natural polysaccharide (hyaluronic acid (HA)) on the photocatalytic activity of methylene blue (MB) was studied both under model conditions (a tryptophan photooxidation reaction in water) and with in vitro experiments on P. aeruginosa and S. aureus bacterial cultures. It was shown spectrophotometrically that, in the presence of HA, an increase in the optical density of the absorption bands λ = 665 nm and 620 nm—which correspond to the monomeric and dimeric forms of the dye, respectively—was observed in the EAS of the dye, while the ratio of the optical density of these bands remained practically unchanged. When adding HA to MB, the intensity of singlet oxygen 1O2 photoluminescence and the degree of fluorescence polarization of MB increase. The observed effects are associated with the disaggregation of molecular associates of the dye in the presence of HA. The maximum increase in the photocatalytic activity of MB (by 1.6 times) was observed in the presence of HA, with concentrations in a range between 0.0015 wt.% and 0.005 wt.%.